Contrasting patterns of insecticide resistance and knockdown resistance (kdr) in the dengue vectors Aedes aegypti and Aedes albopictus from Malaysia - Intan H Ishak; Zairi Jaal; Hilary Ranson; Charles S Wondji (Parasites & Vectors, 2015)
Abstract Background Knowledge on the extent, distribution and mechanisms of insecticide resistance is essential for successful insecticide-based dengue control interventions. Here, we report an extensive resistance profiling of the dengue vectors Aedes aegypti and Aedes albopictus across Malaysia and establish the contribution of knockdown resistance mechanism revealing significant contrast between both species. Methods Aedes mosquitoes were collected from four states in Malaysia in 2010 using ovitraps and tested against six major insecticides using WHO bioassays. Knockdown resistance (kdr) was investigated in both species. Results A moderate resistance to temephos was detected from samples collected in 2010 in Penang, Kuala Lumpur, Johor Bharu and Kota Bharu (1.5 < RR < 3.3). A widespread and multiple resistances was observed in Ae. aegypti particularly against pyrethroids, DDT and bendiocarb. Mosquitoes from Kuala Lumpur consistently had the highest resistance levels and was the only population showing a moderate resistance to malathion (91% mortality). The resistance profile of Ae. albopictus contrasted to Ae. aegypti with full susceptibility to pyrethroids except in Kuala Lumpur where moderate resistance is observed. PBO synergist assays suggest metabolic resistance mechanisms play a major role in resistance in both species. Two kdr mutations, F1534C and V1016G, were detected in Ae. aegypti across Malaysia but neither of these mutations were found in Ae. albopictus. Additionally, signatures of selection were detected on the Voltage-gated sodium channel gene in Ae. aegypti but not in Ae. albopictus. The presence of the 1534C allele was significantly associated with pyrethroid resistance and an additive effect to pyrethroid resistance was observed in individuals containing both kdr alleles. Conclusions Findings from this study will help to design and implement successful insecticide-based interventions against Ae. aegypti and Ae. albopictus to improve dengue control across Malaysia.